First report of Macrocheles scutatiformis (Acari: Macrochelidae) found on insects and soil beneath animal carcasses in Malaysia - Azima Laili Hanifah; Mariana Ahamad; Baharudin Omar; Ahmad Taufik Yusoff; Vishalani Vishnu Narainasamy; Gen Takaku (Universiti Kebangsaan Malaysia, 2015)
In a forensic acarology study, conducted in a secondary forest of Forensic Science Simulation Site, Universiti Kebangsaan Malaysia (UKM) in Bangi, Selangor, six carcasses consisted of three monkeys and three rabbits were placed individually in steel enclosures and observed for 35 days. The carcasses, the soil beneath them and pitfall traps were checked daily for insects and mites. A species of mesostigmatid mite, Macrocheles scutatiformis was discovered and this is a first time reported in Malaysia. There are about 94.0% of Macrocheles present inside the cages of the monkey and rabbit carcasses. Most mites in this study were collected from soil beneath the carcasses, on a dung beetle and a Chrysomya rufifacies larva. Our findings showed that M. scutatiformis have a potential role in forensic investigation involving dead animals perhaps corpses especially during the dry stage of decomposition.